Keberadaan Bisnis Waralaba Berkaitan Dengan HAKI yang Dimiliki Oleh Pihak Pemberi Waralaba Pada Umkm (Di Kota Yogyakarta) - Sumartiah, Siti (AKMENIKA, 2019)
One form of development and expansion of business by using the Franchise system, so rapidly growing supported business expanding increasingly varied. Business approach through Franchise system is one of the strategy of empowering SME to develop business and improve SME in the future. Based on the description of the above mentioned background, it can be formulated the following issues: how the Franchise business regulatory system in the aspect of the agreement / contract, how the form of legal protection terwaralaba and how the efforts undertaken by SMEs as perpetrators of the Franchise in resolving disputes arising from the implementation Franchise agreement In connection with the development and protection of SME business as stipulated through Law No.20 Year 2009 on Small Business which stated that the government intends to seek and empower SMEs in order to compete in facing free trade. The empowerment of MSMEs is done through Partnership program as outlined in PP No.44 of 1997. From the existing Franchise contract, we can see the role of Franchise in arrangement of agreement / contract on Franchise business. But in practice the arrangement of agreement arrangements is more dominant by Franchisors who override the interests of Franchise recipients.